What rare cancers have in common. The making of lists of (very) rare cancers and the coordination of medical work - Pillayre, Héloïse; Besle, Sylvain (Frontiers in Sociology, 2023)
This article aims to understand why medical actors recently published lists of rare and very rare cancers. It argues that these lists constitute boundary objects, whose aim is deal with the organizational challenges raised by precision medicine, which imply to increase the coordination work between various types of actors. It studies four lists of rare and very rare cancers based on interviews with the main actors of these lists and on the basis of an analysis of medical articles in which these lists were published. Our work allows better understanding of the functioning of the recursive standardization process of a boundary object, and, by analyzing how the category of rarity is built at the intersection of both professional and nosographic principles, shows the intertwining of the biomedical, organizational and political aspects on which rests the practice of contemporary precision medicine.